Education for All: Study Case World Bank-Cambodia Scholarship for Education - Sakti, Arauf Aji Harindra (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
This qualitative research conducted with the study case method tries to point out the impact of scholarship led by the World Bank and the Government of Cambodia for secondary school in Cambodia. The cycle of poverty have used to understand the importance of program with financial support to provide education for all and elaborates the correlation between the essence of education to deal with poverty. Despite the positive impact of the scholarship program on pupils to access secondary education, the paper also analyzes the part which cannot be covered only by the scholarship program. Students with low financial support are most likely to drop out without finishing their education level and are at high risk to re-enter the cycle of poverty. It is because they have to actively participate in household economic continuity. Therefore, financial support, in form of scholarship, might be able to reduce the financial burden of education toward the household and prevent students from not finishing secondary school. Even though scholarships can increase student's chances to finish secondary school, yet they cannot deal with the issue of quality education which will be elaborated on in the paper